The Role of Universities in Fostering Research and Development of Social Innovation in Malaysia - Nurhazliyana, Hanafi; Mohamad Pirdaus, yusoh; Jalaluddin, Abdul malek; Mohd Yusof, Hussain; Muhamad Azahar, Abas; Madzlan, Abet; Muhammad Fuad, Abdullah; Kean Hua, Ang (RES MILITARIS, 2023)
Social innovation is a new discipline that aims to bridge the gap between societal requirements and modern technology. The use of social innovation is a strong component for universities that are committed to producing, disseminating, and making knowledge more meaningful. This paper examines the role of universities in supporting social innovations into research and development activities through support from the universities. Using quantitative method through descriptive statistical analysis on the data collected. In the present study, a total of 237 lecturers from eight public universities in Malaysia completed the questionnaire. Result showed, the university's strong support for research that satisfies the requirements of social innovation. The University's role is also to contribute with various types of resources and inputs to foster new social innovation ideas. Therefore, researchers and stakeholders must use the platform to establish collaboration with community to ensure that the research conducted fits societal demands and solves its issues